2017
DOI: 10.1177/0271678x17737984
|View full text |Cite|
|
Sign up to set email alerts
|

Paravascular spaces at the brain surface: Low resistance pathways for cerebrospinal fluid flow

Abstract: Clearance of waste products from the brain is of vital importance. Recent publications suggest a potential clearance mechanism via paravascular channels around blood vessels. Arterial pulsations might provide the driving force for paravascular flow, but its flow pattern remains poorly characterized. In addition, the relationship between paravascular flow around leptomeningeal vessels and penetrating vessels is unclear. In this study, we determined blood flow and diameter pulsations through a thinned-skull cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
277
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(317 citation statements)
references
References 23 publications
31
277
8
1
Order By: Relevance
“…First reported by Iliff et al, the glymphatic pathway involves the “paravascular space,” which drains interstitial fluid and cerebrospinal fluid (CSF) from the para‐arterial space via glial parenchyma to the para‐venous space, finally into the internal cerebral vein. As a low‐resistant drainage pathway, pulsatile paravascular flow generated by the cardiac cycle was observed . Of note, the so‐called “paravascular space” referred to by Iliff is located between the glial limitans and the vascular BM, which is actually VRS where PVMs reside.…”
Section: Pvm Functions In the Normal Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…First reported by Iliff et al, the glymphatic pathway involves the “paravascular space,” which drains interstitial fluid and cerebrospinal fluid (CSF) from the para‐arterial space via glial parenchyma to the para‐venous space, finally into the internal cerebral vein. As a low‐resistant drainage pathway, pulsatile paravascular flow generated by the cardiac cycle was observed . Of note, the so‐called “paravascular space” referred to by Iliff is located between the glial limitans and the vascular BM, which is actually VRS where PVMs reside.…”
Section: Pvm Functions In the Normal Brainmentioning
confidence: 99%
“…As a lowresistant drainage pathway, pulsatile paravascular flow generated by the cardiac cycle was observed. 48 Of note, the so-called "paravascular space" referred to by Iliff is located between the glial limitans and the vascular BM, which is actually VRS where PVMs reside.…”
Section: Lymphatic Clearancementioning
confidence: 99%
“…This was based on analysis of in vivo tracer spreading, using two-photon imaging, and ex vivo fluorescence microscopy on brain slices. Using microsphere tracking, recent work from our group confirmed that at the brain surface, CSF flows along arteries in the direction of blood flow in a pulsatile manner (Bedussi, Almasian, de Vos, VanBavel, & Bakker, 2018). Further confirmation of this flow pattern in a noninvasive manner was provided by the work of Harrison et al (2018).…”
Section: The Paravascular Space and Direction Of Flowmentioning
confidence: 76%
“…Our data show that the paravascular spaces at the level of the meninges is continuous with the subarachnoid space (SAS) and appears as a widening created by meningeal blood vessels. This widening of the SAS is particularly large around arteries, probably because of the rounded shape in comparison to the more flattened veins, and can be observed in both humans and rodents (Bedussi et al, 2018). Weller and Carare refer to perivascular flow along basement membranes that starts at the level of the capillaries and travels upstream along arterial smooth muscle cells.…”
Section: • What Advances Does It Highlight?mentioning
confidence: 99%
“…The main bulk of evidence for the glymphatic pathway has been established via in-vivo rodent experiments. In these experiments, tracers are typically infused in the CSF in rodents at a rate of 0.34-2 µL/min, with a resulting pressure increase of 0.1-2.5 mmHg [31,5,46]. Thus, such tracer experiments may in fact be viewed as infusion tests.…”
Section: Introductionmentioning
confidence: 99%